Relation of infant motor development with nonverbal intelligence, language comprehension and neuropsychological functioning in childhood: a population‐based study. Issue 5 (8th November 2015) - Serdarevic, Fadila; van Batenburg‐Eddes, Tamara; Mous, Sabine E.; White, Tonya; Hofman, Albert; Jaddoe, Vincent W.V.; Verhulst, Frank C.; Ghassabian, Akhgar; Tiemeier, Henning
Abstract: Within a population‐based study of 3356 children, we investigated whether infant neuromotor development was associated with cognition in early childhood. Neuromotor development was examined with an adapted version of Touwen's Neurodevelopmental Examination between 9 and 20 weeks. Parents rated their children's executive functioning at 4 years. At age 6 years, children performed intelligence and language comprehension tests, using Dutch test batteries. At age 6–9 years, neuropsychological functioning was assessed in 486 children using the validated NEPSY‐II–NL test battery. We showed that less optimal neurodevelopment in infancy may predict poor mental rotation, immediate memory, shifting, and planning; but not nonverbal intelligence or language comprehension. Abstract : Early infant motor development, assessed by hands‐on examination at around age 3 months, predicted immediate visual memory and mental rotation in school children in a population‐based study of 3356 children.